2018
DOI: 10.1016/j.jval.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of EuroQol Five-Dimensional Questionnaire, Youth Version (EQ-5D-Y) and EuroQol Five-Dimensional Questionnaire, Three-Level Version (EQ-5D-3L) Health States: The Impact of Wording and Perspective

Abstract: Background: Valuations of health states were affected by the wording of the two instruments (EQ-5D-3L and EQ-5D-Y) and by the perspective taken (child or adult). Objectives: There is a growing demand for value sets for the EQ-5D-Y (EQ-5D instrument for younger populations). Given the similarities between EQ-5D-Y and EQ-5D-3L, we investigated whether valuations of health states were affected by the differences in wording between the two instruments and by the perspective taken in the valuation exercise (child o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(135 citation statements)
references
References 26 publications
5
128
2
Order By: Relevance
“…It has previously been demonstrated that values for health states ascribed by adults differ to corresponding health states ascribed by children. 32 33 However, we used adult weights in the absence of value sets for the EQ-5D-Y. The findings of this study are limited by a small sample.…”
Section: Limitationsmentioning
confidence: 99%
“…It has previously been demonstrated that values for health states ascribed by adults differ to corresponding health states ascribed by children. 32 33 However, we used adult weights in the absence of value sets for the EQ-5D-Y. The findings of this study are limited by a small sample.…”
Section: Limitationsmentioning
confidence: 99%
“…There have been growing interests in the assessment of health-related quality of life (HRQOL) in children and adolescents in recent years. HRQOL instruments designed for adults may not be suitable for younger respondents as they are in a series of cognitive developmental stages and have different perspectives towards the relative importance of HRQOL dimensions [1,2]. As a result, a number of instruments considering specific features of children and adolescents have been developed to evaluate generic or disease-specific HRQOL in these age groups [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the utility measures developed for adult populations may not be representative of children's utility measures as they may not include dimensions that children consider an important aspect of HRQoL [68]. Examples of utility instruments measuring HRQoL from children include Child Health Utility-9D (CHU9D) [69][70][71] and EQ-5D-Y [72,73]. We recommend that future works adopt QALYs or DALYs as the measure of benefit instead of those intermediate outcomes such as 'detected true positive cases' and consider utilities measured by instruments designed for children.…”
Section: Discussionmentioning
confidence: 99%